Analysis of Policy Changing in the History of Chinese Teaching in the U.S.A. - Yanhua, Meng (Sinología hispánica. China Studies Review, 2018)
Based on the analysis of the language policy patterns of the U.S.A., the article combs on its history of Chinese teaching. It’s proposed that the 130 years of history can be divided into four periods according to different policy patterns. These are nonintervention policy before the Second World War, priority policy during the war, containment- priority- diversity policies after the war, and priority policy in the 21st century. Based on these analyses, a revised policy pattern mode is provided for analyzing foreign language policy.